Pregnancy Outcomes of Women in Two Health Institutes; A Cross-Sectional Study in Pakistan - Asima Munawar, Khadeeja Mustafa, Sohaib Arif, Romesa Atteeq, Emama Bhatti, Fizzah Usman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Complications that could be fatal can affect nearly 15% of pregnant women. As a result, it will be helpful to direct the appropriate intervention if a high-risk pregnancy is identified early on. Objectives: This study was aimed to ascertain the outcomes of pregnancies among pregnant women. Methods: In this study, age groups of 20-40 years of women were involved, among them, 60 women from each hospital participated. The majority of women were from rural areas. The occupation of majority of women husband in DHQ was farming (33.33%), followed by laborer (40%), teaching (16.65%) and trading (10%), while majority of husbands of patients in KTMC were laborer (38.33%) followed by farming (36.66%), teaching (13.33%) and trading (11.66%). Results: The normal weight of children in DHQ and KTMC was recorded 75 and 68.33%, respectively. In DHQ and KTMC, 50 and 38.33% children born alive, respectively while 26.66 and 35% abortions occurred, respectively. Neonatal outcome was linked to pregnancy complications and perinatal morbidity. Practical implications: This study focused on the neonatal health and the pregnancy outcome of the pregnant women. Improvement in vaginal birth, improvement of neonatal birth weight but caesarean section in high-risk mothers was analyzed in this study. Conclusion: The majority of maternal morbidities could be avoided if the mother had access to timely and appropriate healthcare during her pregnancy. As a result, proper care and prompt referral can help reduce perinatal mortality and morbidity and possibly improve maternal outcomes. Keywords: Pregnancy; Outcomes; Complications; Low birth weight; prenatal care